0658 The Effect of Text Message Reminders on Positive Airway Pressure Adherence in Veterans With Obstructive Sleep Apnea. (27th May 2020) - Al Saleh, Q; Kim, D; Jordan, K; Balish, M; Kataria, L
Abstract: Introduction: Adherence to positive airway pressure (PAP) therapy continues to be a challenge. The main objective of this study was to determine whether mobile text-message reminders increased PAP adherence in veterans with obstructive sleep apnea. Methods: This is a retrospective study of 25 patients with poor adherence to PAP therapy who used the Veterans Affairs ANNIE app to receive nightly mobile text message reminders. PAP adherence was measured at baseline, 1, and 3 months. A one-way repeated measures ANOVA was used to compare the effect of time on PAP adherence, specifically the percentage of overall days used and percentage use >4 hours. A two-way repeated measures ANOVA without replication was used to determine the effects of AHI severity and time on PAP adherence. Results: Our sample demographics included a mean age of 59 ±12 years, mean BMI of 33.5% ±5.4, and mean AHI of 26.3 ±25.4. The mean PAP overall percentage use and mean use >4 hours respectively were 32% ± 27 and 18% ± 19 at baseline, 66% ± 27 and 45% ± 30 at 1 month, and 54% ±32 and 37% ± 30 at 3 months. After three months of receiving nightly text-message reminders, there was a statistically significant effect of time on percentage overall PAP use, F (2, 48)=21.54, p=2.10E-07, as well as in the percentage PAP use >4 hours, F (2, 48)=22.05, p=1.61E-07. A two-way repeated measures ANOVA without replication yielded a main effect of the interaction of time with PAP adherence, F (2, 48)=22, p=<0.0001. AHI severity was not a significant factor. Conclusion: Nightly text message reminders significantly improved PAP adherence from baseline to 3 months. Though PAP adherence was not optimal, it doubled initially in our sample. Further studies are warranted to determine how text-messages can be used long term to improve adherence. Support: Nil